Elastic Stresses in Thin-Walled Torsional Structures Designed with SADSF Method - Ireneusz MARKIEWICZ (Engineering Transactions, 2014)
The paper presents general conclusions arising from FEM analyses of elastic properties of thin-walled structures designed with the application version of the statically admissible discontinuous stress fields (SADSF) method. The analyses have been carried out as a part of a large-scale research program, whose main objective is conclusive verification of practical usefulness of the SADSF method in design. The present state of development of the method’s application software is so advanced that it allows one to design even very complicated thin- walled structures composed of plane elements. This is a particular class of structures to which the Saint Venant’s principle is not applicable [3, 4], and the methods based on consecutive iterative improvements should be applied with due caution. In the SADSF method one does not use iterations, and the method can be applied already at the stage when only boundary conditions are known [3, 4]. Unfortunately, the method is an approximate one and does not apply to the elastic range of stress that usually exists in exploitation conditions. On the basis of analyses carried out for several dozen cases of thin-walled structures de- signed with the SADSF method we can state, among other things, that in these structures there are dominating membrane states, deformations remain small, equivalent stress fields are well equalized also along free borders, stress concentrations are relatively low, and maximal levels of equivalent stresses are approximately the same in all component elements. It has also been proven that the structures designed with the SADSF method may have strength properties even several dozen times better that those of structures designed traditionally. The obtained conclusions are presented on the basis of three selected examples of original, which in this case have open-section structures (see e.g. [11]) designed to carry torsional load [3, 4].